Application of Mirath sheriah in Kakamega County - Ngeri H.B Gimway (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2024)
This study, conducted in Kakamega County examined whether or not mirath is applied with regard to women; if there were any factors that promoted or impeded the application of mirath in the County and sort to identify strategies for implementation of mirath in the context of Islamic teachings and the Constitution of Kenya 2010. The study was guided by the Feminist Conflict Theory (propounded by Karl Max 1818-1883). Purposive sampling identified respondents from among the various segments of Muslims living in the County. The study employed a qualitative cross-sectional descriptive research design. Primary data was collected using interviews and focus group discussions from purposively sampled key respondents who included: Kadhi, Imams, widows, widowers, sons and daughters whose parents are deceased. Interview schedules and focus group discussion were the tools used. Secondary data was collected from the internet, journals and books. Data collected was analyzed thematically. This study examined the application of Islamic laws of inheritance with particular reference to Luhya indigenous Muslims and specific reference to women in Kakamega County. The findings demonstrated that the Luhya inheritance rules are patriarchal thereby favouring male children over females despite the advent of Islam in the region. The male chauvinistic tendencies in the Luhya community have pushed Muslim women to a subordinate and inferior position hence their intrinsic value is negated. The study established that Luhya inheritance rules are so entrenched that they have not been fully altered or replaced by the Shariah. Many respondents consented that Luhya Muslims still practice the indigenous patriarchal inheritance rules though they have adopted other Islamic beliefs and practices